High-accuracy crRNA array assembly strategy for multiplex CRISPR - Xiangtong Zhao; Lixian Yang; Peng Li; Zijing Cheng; Yongshi Jia; Limin Luo; Aihong Bi; Hanchu Xiong; Haibo Zhang; Hongen Xu; Jinrui Zhang; Yaodong Zhang (Molecular Therapy: Nucleic Acids, 2025)
Simultaneous targeting of multiple loci with the CRISPR system, a tool known as multiplex CRISPR, offers greater feasibility for manipulating and elucidating the intricate and redundant endogenous networks underlying complex cellular functions. Owing to the versatility of continuously emerging Cas nucleases and the use of CRISPR arrays, multiplex CRISPR has been implemented in numerous in vitro and in vivo studies. However, a streamlined, practical strategy for CRISPR array assembly that is both convenient and accurate is lacking. Here, we present a novel, highly accurate, cost-, and time-saving strategy for CRISPR array assembly. Using this strategy, we efficiently assembled 12 CRISPR RNAs (crRNAs) (for AsCas12a) and 15 crRNAs (for RfxCas13d) in a single reaction. CRISPR arrays driven by Pol II promoters exhibited a distinct expression pattern compared with those driven by Pol III promoters, which could be exploited for specific distributions of CRISPR intensity. Improved approaches were subsequently designed and validated for expressing long CRISPR arrays. The study provides a flexible and powerful tool for the convenient implementation of multiplex CRISPR across DNA and RNA, facilitating the dissection of sophisticated cellular networks and the future realization of multi-target gene therapy.